Analysis of the influence of bromazepam on cognitive performance through the visual evoked potential (P300) Análise da influência do bromazepam na performance cognitiva através do potencial evocado visual (P300) - Fernanda Puga; Heloisa Veiga; Maurício Cagy; Kaleb McDowell; Roberto Piedade; Pedro Ribeiro (Arquivos de Neuro-Psiquiatria)
Benzodiazepines have been used in the pharmacological treatment of anxiety for over four decades. However, very few studies have combined bromazepam and event-related potentials (ERP). The present study aimed at investigating the modulatory effects of this drug on brain dynamics. Specifically, the effects of bromazepam (3mg) on the P300 component of the ERP were tested in a double-blind experiment. The sample, consisting of 15 healthy subjects (7 male and 8 female), was submitted to a visual discrimination task, which employed the "oddball" paradigm. Electrophysiological (P300) and behavioral measures (stroop, digit span, and reaction time) were analyzed across three experimental conditions: placebo 1, placebo 2, and bromazepam. Results suggest that the effects of bromazepam (3mg) on cognitive processes are not apparent. In spite of what seems irrefutable in current literature, bromazepam did not produce evident effects on the behavioral and electrophysiological variables analyzed. Benzodiazepínicos têm sido utilizados no tratamento farmacológico da ansiedade há mais de quatro décadas. No entanto, poucos estudos têm combinado bromazepam e potencial evocado relacionado a evento (PRE). O presente estudo teve por objetivo investigar os efeitos modulatórios desta droga na dinâmica cerebral. Especificamente, os efeitos de 3mg de bromazepam no componente P300 do PRE foram analisados em um experimento duplo-cego. A amostra consistiu de 15 sujeitos sadios (7 homens e 8 mulheres), submetidos a uma tarefa de discriminação visual utilizando o paradigma "oddball". Medidas eletrofisiológicas (P300) e comportamentais (stroop, digit span, e tempo de reação) foram analisadas em três condições experimentais: placebo 1, placebo 2 e bromazepam. Os resultados sugerem que os efeitos de 3mg de bromazepam em processos cognitivos não são aparentes. Apesar do que parece irrefutável na literatura, o bromazepam não produziu efeitos evidentes nas variáveis comportamentais e eletrofisiológicas analisadas.